The persistence of social inequality in adult mortality in rural Spain, death cohorts 1546-2010 - Francisco J. Marco-Garcia; Víctor A. Luque de Haro (European Historical Economics Society (EHES), 2023)
This paper analyses social inequality in adult mortality over the last 500 years in rural Aragon (Spain). It uses individual-level microdata corresponding to more than 20,000 individuals whose socioeconomic status, age at death and other family, cultural and environmental variables are known. Using advanced statistical techniques (mainly event history analysis), it follows all individuals who died after the age of seven years in 17 villages throughout their lives. This study is focused on observing the evolution of inequality in mortality by SES over a period of 500 years, deepening and relating it to the debates present in the historiography. As it is a pioneer study in connecting adult mortality with SES for almost five centuries, it enables us to verify the persistence of social inequality in death in rural Spain, which contrasts with the results obtained in northern European countries where these differences only emerged from the late nineteenth or early twentieth century onwards.
Keywords: I14; N33; J11; 330; Adult mortality; socioeconomic differences; inequality; Spain